2021
DOI: 10.3389/fimmu.2021.636775
|View full text |Cite|
|
Sign up to set email alerts
|

Humanized Mice for the Evaluation of Novel HIV-1 Therapies

Abstract: With the discovery of antiretroviral therapy, HIV-1 infection has transitioned into a manageable but chronic illness, which requires lifelong treatment. Nevertheless, complete eradication of the virus has still eluded us. This is partly due to the virus’s ability to remain in a dormant state in tissue reservoirs, ‘hidden’ from the host’s immune system. Also, the high mutation rate of HIV-1 results in escape mutations in response to many therapeutics. Regardless, the development of novel cures for HIV-1 continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 232 publications
(254 reference statements)
0
12
0
Order By: Relevance
“…Because HIV-1 elite controllers represent a minor portion of PLWH, it would be beneficial to establish animal models such as humanized mice and SIV-infected NHP with immune responses that mirror those of elite controllers. In the humanized mouse model, the immune system is reconstituted with human immune cells ( 79 ). Whereas mice are not susceptible to HIV-1 infection, numerous groups confirmed that HIV-1 can replicate in various humanized mice models ( 80 83 ), which are widely used to examine promising immunotherapies ( 84 ), latency reversing agents ( 85 ), and gene-editing of HIV-1 proviruses in vivo ( 86 , 87 ).…”
Section: Animal Models For Hiv-1 Elite Controllersmentioning
confidence: 99%
See 1 more Smart Citation
“…Because HIV-1 elite controllers represent a minor portion of PLWH, it would be beneficial to establish animal models such as humanized mice and SIV-infected NHP with immune responses that mirror those of elite controllers. In the humanized mouse model, the immune system is reconstituted with human immune cells ( 79 ). Whereas mice are not susceptible to HIV-1 infection, numerous groups confirmed that HIV-1 can replicate in various humanized mice models ( 80 83 ), which are widely used to examine promising immunotherapies ( 84 ), latency reversing agents ( 85 ), and gene-editing of HIV-1 proviruses in vivo ( 86 , 87 ).…”
Section: Animal Models For Hiv-1 Elite Controllersmentioning
confidence: 99%
“…Although mice reconstituted with HLA-B*57 positive cells demonstrated better control of HIV-1 replication, they could not suppress HIV-1 replication to the point where viral loads would be lower than the limit of detection, in contrast to human ECs. It is important to note that their humanized mice model poorly reconstitute innate immune cells ( 79 ), and robust CD8+ T cell responses have been positively associated with more successful reconstitution of monocytes in humanized mouse models ( 91 ). Therefore, one possible explanation for why humanized mice could not achieve HIV-1 control is that EC innate immune responses were not recapitulated in their model.…”
Section: Animal Models For Hiv-1 Elite Controllersmentioning
confidence: 99%
“…NOD/Shi-scid/IL-2Rγnull (NSG) immune-deficient mice were engrafted with hematopoietic stem cells (CD34 + HSC) derived from 2 donors. The NSG-HSC mouse model is a well-established platform, widely used to investigate and validate the effects of anti-HIV therapies, possessing a fully differentiated human immune system that can support HIV replication and reservoir establishment, and reconstituting intact innate immunity capable of response ( 66 , 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human PSC-derived hematopoietic progenitors and microglia have been transplanted to the rodent brain and upon engraftment, these cells can acquire molecular properties that are more representative of in vivo populations than is typically observed in vitro ( 192 194 ). Similar strategies have been used to “humanize” animals that are otherwise resistant to infection of some viruses, such as HIV ( 195 ). Transplantation of human progenitors early in development can also facilitate investigations of viral pathogenesis in the developing brain.…”
Section: Two-dimensional Culturesmentioning
confidence: 99%